1991
DOI: 10.2307/3869162
|View full text |Cite
|
Sign up to set email alerts
|

Stress-Induced Translational Control in Potato Tubers May Be Mediated by Polysome-Associated Proteins

Abstract: Potato tubers exhibit distinct responses to wounding and hypoxia that include selective translation of stress-induced mRNAs. Newly synthesized wound-response mRNAs are bound to polysomes, whereas preexisting mRNAs are displaced and degraded. mRNAs that are induced and translated during hypoxic conditions are bound to ribosomes as expected. However, preexisting wound-response mRNAs whose translation is inhibited during hypoxia remain bound to polysomes, indicating that there are at least two distinct mechanisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
1

Year Published

1992
1992
2003
2003

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 0 publications
1
29
1
Order By: Relevance
“…The Plant Cell wound-associated proteins is elevated (Crosby and Vayda, 1991). Our findings suggest that during pathogen-induced PCD in tobacco, the expression of cAPX is inhibited via a similar mechanism.…”
mentioning
confidence: 59%
See 1 more Smart Citation
“…The Plant Cell wound-associated proteins is elevated (Crosby and Vayda, 1991). Our findings suggest that during pathogen-induced PCD in tobacco, the expression of cAPX is inhibited via a similar mechanism.…”
mentioning
confidence: 59%
“…Inhibition of protein translation is known to occur during many stress conditions in plants (Crosby and Vayda, 1991;Cohen and Mayfield, 1996;Gallie, 1996). During recovery from drought stress in pea, the expression of cAPX was found to be controlled by the association of cAPX transcripts with polysomes (Mittler and Zilinskas, 1994), suggesting that the expression of cAPX was regulated post-transcriptionally at the level of translation initiation.…”
Section: Association Of Capx Transcripts With Polysomesmentioning
confidence: 99%
“…For example, enolase mIWA levels in tomato and Arabidopsis roots were estimated to be 10-to 20-fold higher than in leaves, even though enolase protein levels appeared constant in a11 tissues (Van Der Straeten et al, 1991). In addition, posttranscriptional regulation has been reported for other glycolytic enzymes under conditions of anaerobic stress, such as aldolase (Hake et al, 1985), Suc synthase (McElfresh and Chourey, 1988;Talierio and Chourey, 19891, and wound-inducible genes (Crosby and Vayda, 1991). Modifications in the phosphorylation status of a 31-kD ribosomal protein (Bailey-Serres and Freeling, 1990) and the translational initiation factor eIF-4A (Webster et al, 1991) have been reported and are thought to be associated with translational repression events during anoxia stress.…”
Section: Discussionmentioning
confidence: 99%
“…Modifications of distinct ribosomal proteins or of proteins interacting with them, for example by phosphorylation or dephosphorylation, have been reported to occur under diverse stress conditions (Scharf and Nover, 1982;Nover and Scharf, 1984;Bailey-Serres and Freeling, 1990;Crosby and Vayda, 1991;Apuya and Zimmerman, 1992) and might also be required to ensure the selectivity of JIP protein synthesis.…”
Section: Translational Control: Ribosomes Discriminate Against Rbcs Amentioning
confidence: 99%